Portraits in the Andes : Photography and Agency, 1900-1950 - Coronado, Jorge (Illuminations (Pittsburgh, Pa.), 2018)
Portraits in the Andes examines indigenous and mestizo self-representation through the medium of photography from the early to mid twentieth century. As Jorge Coronado reveals, these images offer a powerful counterpoint to the often-slanted, predominant view of indigenismo produced by the intellectual elite. Photography offered an inexpensive and readily available technology for producing portraits and other images that allowed lower- and middle-class racialized subjects to create their own distinct rhetoric and vision of their culture. The powerful identity-marking vehicle that photography provided to the masses has been overlooked in much of Latin American cultural studies--which have focused primarily on the elite's visual arts. Coronado's study offers close readings of Andean photographic archives from the early- to mid-twentieth century, to show the development of a consumer culture and the agency of marginalized groups in creating a visual document of their personal interpretations of modernity.